Analisis Peningkatan Nilai Kemandirian Siswa Melalui Model Value Clarification Technique (VCT) Dalam Pembelajaran Pendidikan Pancasila Kelas IV di SD - SABRINA NOOR SYAKIRAH BACHTIAR PUTRI; Tunjungsari Sekaringtyas; Endang Wahyudiana (STKIP Subang, 2025)
Character education is an important aspect of learning in elementary schools, especially in shaping the value of student independence. This study aims to analyze the application of the Value Clarification Technique (VCT) Model in increasing the value of student independence in learning Pancasila Education class IV in elementary school. The problem raised is the lack of instilling the value of autonomy in students which can affect the student behavior. The method used in this research is a literature study by analyzing various relevant literature regarding the application of VCT in character education and Pancasila learning. The literature used includes journal articles and previous studies that discuss theories and best practices in increasing student independence through the VCT model. The results showed that the application of the VCT Model can strengthen students independence values through a value clarification process that involves students in understanding and decision-making. This study concludes that the VCT model has great potential in increasing student independence and can be adapted to learning Pancasila Education in elementary schools.